The Development of Student Worksheet Learning Media Based on Project Based Learning Materials of The Prophet Hijrah to Madinah and The Struggle of Khulafa'u Ar-Rasyidin (APPLICATION: Applied science in Learning Research, 2022)
His study aims to determine the process of developing and qualifying student worksheets (LKPD) based on Project Based Learning on the material of the Prophet's Hijrah to Medina and the Struggle of Khulafa'u Ar - Rasyidin. LKPD Development Research adapting the ADDIE model includes the stages of analysis, design, development, implementation and evaluation. The research instruments used were observation sheets, interviews, student response questionnaires, product development validation results by media experts, designs, and materials followed by teacher assessments and responses to students as well as trials to students. Based on the results obtained. positive. Based on the results of the posttest assessment, 88% of students scored above the KKM. Based on these data, student worksheets (LKPD) based on Project Based Learning on the material of the Prophet's Hijrah to Medina and the Struggle of Khulafa'u Ar - Rasyidin are suitable for use as PAI learning media..